Student’s Perception Towards the Use of Jeopardy Game in English Learning - Alfiyah Rusdiyana; Slamet Setiawan; Ahmad Munir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The present study aims to determine the student's perception towards the use of Jeopardy Game, and also investigates how the teacher uses Jeopardy Game in English learning. This research study was used a qualitative study conducted in-state senior high school level in Surabaya. A close-ended questionnaire was used to obtain the data. The results show that Jeopardy Game makes English learning more alive, comfortable, enjoyable, fun, and interesting. It also boosts the student's motivation in learning English. Jeopardy Game also enhances the student's vocabulary knowledge, recalls the previous materials, improves the student's speaking skill and develop the student's critical thinking. This study suggests using Jeopardy Game in the learning process since many benefits in increasing the student's engagement in the classroom. Keywords: Classroom Games, English Learning, Jeopardy Game, Student’s Perception